Manajemen Ekonomi Keluarga Pasca Kenaikan Harga Bahan Pokok (Studi kasus Ibu Rumah Tangga di Desa Betung Bedarah Timur, kecamatan Tebo Ilir) - Resty Wahyu Ramadhani; Putri Apria Ningsih; Victor Diwantara (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
In managing family management, the one who acts as the manager is usually the housewife. To be able to manage family finances professionally. Research with the title: "Family Economic Management After the Increase in Prices of Basic Materials (Case Study of Housewives in Betung Bedarah Timur Village, Tebo Ilir District). This research uses qualitative research methods. The types and sources of data needed are primary data and secondary data. With 9 informants who were interviewed, namely housewives. The research results show that housewives' understanding of family economic management is very simple. The absence of a housewife regulates the family economy after the increase in prices of basic commodities. There are no income posts and expenditure posts, and expenses often exceed income. There is no influence of internalization on family financial management. And the impact of rising prices of basic commodities has a big impact on housewives' purchasing power.